The impact of gas disc flaring on rotation curve decomposition and revisiting baryonic and dark matter relations for nearby galaxies. Issue 3 (7th June 2022) - Mancera Piña, Pavel E; Fraternali, Filippo; Oosterloo, Tom; Adams, Elizabeth A K; Teodoro, Enrico di; Bacchini, Cecilia; Iorio, Giuliano
ABSTRACT: Gas discs of late-type galaxies are flared, with scale heights increasing with the distance from the galaxy centres and often reaching kpc scales. We study the effects of gas disc flaring on the recovered dark matter halo parameters from rotation curve decomposition. For this, we carefully select a sample of 32 dwarf and spiral galaxies with high-quality neutral gas, molecular gas, and stellar mass profiles, robust H i rotation curves obtained via 3D kinematic modelling, and reliable bulge-disc decomposition. By assuming vertical hydrostatic equilibrium, we derive the scale heights of the atomic and molecular gas discs and fit dark matter haloes to the rotation curves self-consistently. We find that the effect of the gas flaring in the rotation curve decomposition can play an important role only for the smallest, gas-dominated dwarfs, while for most of the galaxies, the effect is minor and can be ignored. We revisit the stellar- and baryon-to-halo mass relations ( M * – M 200 and M bar – M 200 ). Both relations increase smoothly up to M_200 ≈ 10^12 M_, with galaxies at this end having high M * / M 200 and M bar / M 200 ratios approaching the cosmological baryon fraction. At higher M 200, the relations show a larger scatter. Most haloes of our galaxy sample closely follow the concentration–mass ( c 200 – M 200 ) relation resulting from N -body cosmological simulations. Interestingly, the galaxies deviating above and below the relation have the highest and lowest stellar and baryon factions, respectively, which suggests that the departures from the c 200 – M 200 law are regulated by adiabatic contraction and an increasing importance of feedback.